Electrolytic capacitor and method of manufacturing the same

CN122996493APending Publication Date: 2026-10-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580021767.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

固体电解质层含有导电性高分子

Benefits of technology

[0027]根据本发明,能够提升电解电容器的容量和耐久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996493A_ABST
    Figure CN122996493A_ABST
Patent Text Reader

Abstract

An electrolytic capacitor includes an anode body having a porous portion with at least a portion of a surface thereof covered with a dielectric layer, and a solid electrolyte layer covering at least a portion of the dielectric layer, the solid electrolyte layer containing a sulfur element-containing conductive polymer, the sulfur element-containing conductive polymer filling at least a portion of voids of the porous portion, and a count value S5 of sulfur element detected by an electron beam microanalyzer at a position having a depth of 5 μm from a main surface of the porous portion being 12500 or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference of related applications

[0002] This invention claims priority to Japanese Patent Application No. 2024-052417 filed with the Japan Patent Office on March 27, 2024, the entire contents of which are incorporated herein by reference. Technical Field

[0003] This invention relates to electrolytic capacitors and methods for manufacturing the same. Background Technology

[0004] Patent Document 1 proposes "a method for manufacturing an electrolytic capacitor, characterized in that the manufacturing method comprises: a first step of fabricating a capacitor element body, the capacitor element body including an anode having a dielectric oxide film, a cathode and a spacer disposed between the anode and the cathode; a second step of preparing a mixture, wherein a first conductive polymer is dispersed in a solvent and a second conductive polymer is dissolved in a solvent; and a third step, wherein the mixture is impregnated into the capacitor element body and then subjected to heat treatment, thereby forming a conductive polymer layer in the voids of the capacitor element body, and wherein the concentration of the first conductive polymer in the mixture is less than 5 times the concentration of the second conductive polymer."

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 2022-161723 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] An electrolytic capacitor comprises: an anode having a porous portion of its surface covered by a dielectric layer, and a solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer contains a conductive polymer. The conductive polymer permeates into a portion of the voids in the porous portion.

[0010] However, it is difficult to fill the pores of porous sections with conductive polymers, and there is room for improvement in terms of increasing capacitance and durability of electrolytic capacitors.

[0011] Methods for solving problems

[0012] One aspect of the present invention relates to an electrolytic capacitor comprising: an anode having a porous portion of its surface covered by a dielectric layer, and a solid electrolyte layer covering at least a portion of the dielectric layer.

[0013] The aforementioned solid electrolyte layer contains a conductive polymer containing sulfur.

[0014] The aforementioned sulfur-containing conductive polymer fills at least a portion of the voids in the aforementioned porous portion.

[0015] The sulfur element count S5, detected by an electron beam microanalyzer at a depth of 5 μm from the main surface of the porous section, is 12500 or higher.

[0016] Another aspect of the present invention relates to an electrolytic capacitor comprising: an anode having a porous portion of its surface covered by a dielectric layer, and a solid electrolyte layer covering at least a portion of the dielectric layer.

[0017] The aforementioned solid electrolyte layer contains a conductive polymer containing sulfur.

[0018] The aforementioned sulfur-containing conductive polymer fills at least a portion of the voids in the aforementioned porous portion.

[0019] The ratio (S5 / S1) of the sulfur element count value S5 detected by an electron beam micro analyzer at a depth of 5 μm from the main surface of the porous portion to the sulfur element count value S1 detected by an electron beam micro analyzer at a depth of 1 μm from the main surface of the porous portion is 0.15 or higher.

[0020] Another aspect of the present invention relates to a method for manufacturing an electrolytic capacitor, comprising:

[0021] A process for preparing an anode body, the anode body having a porous portion on its surface covered by a dielectric layer; and

[0022] The process of forming a solid electrolyte layer, wherein the solid electrolyte layer covers at least a portion of the aforementioned dielectric layer.

[0023] The aforementioned solid electrolyte layer contains a conductive polymer containing sulfur.

[0024] The aforementioned sulfur-containing conductive polymer fills at least a portion of the voids in the aforementioned porous portion.

[0025] The ratio (S5 / S1) of the sulfur element count value S5 detected by an electron beam micro analyzer at a depth of 5 μm from the main surface of the porous portion to the sulfur element count value S1 detected by an electron beam micro analyzer at a depth of 1 μm from the main surface of the porous portion is 0.15 or higher.

[0026] Invention Effects

[0027] According to the present invention, the capacitance and durability of electrolytic capacitors can be improved. Attached Figure Description

[0028] Figure 1 This is a cross-sectional schematic diagram of an electrolytic capacitor according to one embodiment of the present invention.

[0029] Figure 2 A graph showing the relationship between the depth of the anode body of an electrolytic capacitor from the main surface of the porous portion and the sulfur (S) count value detected by an electron beam microanalyzer according to one embodiment of the present invention. Detailed Implementation

[0030] Although novel features of the invention are described in the appended claims, the invention will be further understood in terms of its composition and content, in conjunction with other objects and features of the invention, through the following detailed description with reference to the accompanying drawings.

[0031] The following examples illustrate embodiments of the present invention, but the present invention is not limited to the examples described below. In the following description, specific values, materials, etc., are illustrated, but other values, materials, etc., can be applied as long as the effects of the present invention are achieved. It should be noted that known capacitor components can also be applied to components other than the characteristic parts of the present invention. In this specification, when referred to as the "range of value A to value B," this range includes both value A and value B. When multiple materials are illustrated, one can be selected for use alone, or two or more can be used in combination.

[0032] Furthermore, the present invention also includes a combination of matters described in two or more claims selected from the plurality of claims listed in the appended claims. In other words, matters described in two or more claims selected from the plurality of claims listed in the appended claims can be combined, provided that no technical contradiction arises.

[0033] The "electrolytic capacitor" of this invention is a "solid electrolytic capacitor" that uses a conductive polymer as a solid electrolyte, and may further include a liquid. An "electrolytic capacitor" containing a liquid may also be called a "solid-liquid electrolytic capacitor" or a "(solid-liquid) composite electrolytic capacitor." The term "capacitor" may also be changed to "capacitance."

[0034] The electrolytic capacitor of the present invention comprises: an anode having a porous portion on its surface covered by a dielectric layer, and a solid electrolyte layer covering at least a portion of the dielectric layer. The smallest unit of such a structure comprising an anode, a dielectric layer, and a solid electrolyte layer is also referred to as a capacitor element. That is, the electrolytic capacitor comprises at least one capacitor element.

[0035] There are no particular limitations on the shape of a capacitor element. A capacitor element only needs to have an anode and a cathode. The anode body constitutes the anode section. The solid electrolyte layer constitutes the cathode section. The cathode section may include a cathode lead-out layer.

[0036] The solid electrolyte layer may have a first part and a second part. The first part is the portion that fills the voids in the porous section. The second part is the portion that protrudes from the main surface of the porous section.

[0037] In the electrolytic capacitor of the present invention, the solid electrolyte layer contains a sulfur-containing conductive polymer. The sulfur-containing conductive polymer (hereinafter also referred to as "S-containing conductive polymer") fills at least a portion of the voids in the porous portion and forms a first portion. Here, the solid electrolyte layer satisfies at least one of the following conditions (A) and (B).

[0038] Condition (A): The sulfur count value S5 detected by an electron beam microanalyzer (EPMA) at a depth of 5 μm from the main surface of the porous section is greater than 12500.

[0039] The count value S5 can also be above 15000. It should be noted that in the case of conventional electrolytic capacitors, the count value S5 is usually below 11000.

[0040] Condition (B): The ratio (S5 / S1) of the sulfur count value S5 detected by EPMA at a depth of 5 μm from the main surface of the porous part to the sulfur count value S1 detected by EPMA at a depth of 1 μm from the main surface of the porous part is 0.15 or higher.

[0041] The S5 / S1 ratio can also be above 0.18. It should be noted that in the case of conventional electrolytic capacitors, the S5 / S1 ratio of sulfur is usually below 0.14.

[0042] The sulfur content detected by EPMA reflects the amount of sulfur-containing conductive polymer contained in the first part of the solid electrolyte layer. Satisfying at least one of conditions (A) and (B) means that a sufficient amount of sulfur-containing conductive polymer is distributed in the pores of the porous portion. By satisfying at least one of conditions (A) and (B), the capacitance achievement rate and durability of the electrolytic capacitor are simultaneously improved.

[0043] The capacitance achievement rate of an electrolytic capacitor is the ratio of the capacitance of the anode (capacitance before the formation of a solid electrolyte layer) when a rated voltage of 120 Hz is applied in a 15% by mass ammonium adipate aqueous solution to the capacitance after the formation of a solid electrolyte layer.

[0044] As indicators of the durability of electrolytic capacitors, charge-discharge characteristics and heat resistance durability can be used. Charge-discharge characteristics can be evaluated by the change in capacitance (ΔCap) of the electrolytic capacitor before and after repeating 10,000 charge-discharge cycles (ON (applied rated voltage) / OFF = 1 second / 1 second). Heat resistance durability can be evaluated by the equivalent series resistance (ESR) of the electrolytic capacitor after high-temperature storage (500 hours at 145°C).

[0045] The following explains how to calculate the sulfur count based on EPMA at an arbitrary depth of N μm from the main surface of the porous section.

[0046] (1) Preparation of the cross-section of the capacitor element

[0047] First, a capacitor element or product to be measured is prepared. Next, the capacitor element or product is cut along a direction perpendicular to its main surface to form a porous cross-section (hereinafter referred to as a "cross-section specimen"). In the case of a capacitor element, a thermosetting resin can be filled and cured. For example, the cross-section specimen can be obtained using ion milling, FIB (Focused Ion Beam) method, wet grinding, etc. Among these, wet grinding may result in the dissolution of water-soluble sulfur compounds, therefore ion milling is preferred. In the cross-section specimen, a metallic framework constituting the porous portion, a dielectric layer covering at least a portion of its surface, and a conductive polymer constituting the solid electrolyte layer are observed.

[0048] (2) Image of cross-sectional specimens using a scanning electron microscope (SEM)

[0049] Next, the cross-sectional specimen was observed using SEM. The SEM observation was performed at approximately 500 to 1500 times magnification, which allowed for observation of the metal framework constituting the porous portion, the dielectric layer covering at least a portion of its surface, and the conductive polymer constituting the solid electrolyte layer.

[0050] (3) Elemental analysis

[0051] While observing the SEM images, the range for elemental analysis using EPMA was determined. A 100 μm × 80 μm region was defined for line analysis, in a manner that the metal framework constituting the porous portion, the dielectric layer covering at least a portion of its surface, and the conductive polymer constituting the solid electrolyte layer were all included.

[0052] (4) Analysis conditions

[0053] An example of SEM-EPMA measurement conditions is shown.

[0054] As the processing equipment, the Hitachi High-Tech Corporation ArBlade (registered trademark) 5000 ion milling unit was used. The processing conditions were an acceleration voltage of 6kV and a discharge voltage of 1.5kV.

[0055] The measuring apparatus used was the EPMA-8050G manufactured by Shimadzu Corporation. The accelerating voltage during analysis was 8 kV, and the accelerating voltage for SEM was set to 15 kV. The electron beam current was 5 nA, the analysis region was 80 μm, the integration time was 20 s / point, and the measurement interval was 1 μm.

[0056] Under condition (B), it can be assumed that not only is a sufficient amount of S-containing conductive polymer filled deep into the pores, but also that the amount of conductive polymer varies with an almost ideal gradient along the depth direction from the main surface of the porous section. Therefore, further improvements in capacity and durability can be expected.

[0057] It should be noted that if the amount of conductive polymer in the deep pores is the same as that near the surface, although the capacity is improved, it may sometimes cause disadvantages in other ways. For example, there is a possibility of increased leakage current or decreased heat resistance and durability.

[0058] The electrolytic capacitor of the present invention may further satisfy the following condition (C).

[0059] Condition (C): The ratio of sulfur count values ​​S10 to S5 (S10 / S5) detected by EPMA at a depth of 10 μm from the main surface of the porous section is 0.3 or higher.

[0060] The S10 / S5 ratio can also be above 0.40. In this case, it can be assumed that the amount of conductive polymer varies in the depth direction from the main surface of the porous portion, forming a gradient that is closer to the ideal.

[0061] On the other hand, the ratio of S10 to S5 (S10 / S5) can be 0.5 or less, 0.47 or less, or 0.4 or less. In this case, S5 is large enough to ensure high capacity, and the amount of conductive polymer deep within the pores is moderately limited. Therefore, leakage current is suppressed, and the balance between capacity and durability is improved.

[0062] S-containing conductive polymers can also include self-doped conductive polymers (hereinafter also referred to as "conductive polymer A"). Self-doped conductive polymers (conductive polymer A) are soluble in liquid media, thus easily penetrating deep into the pores of porous structures.

[0063] Self-doped conductive polymers refer to polymers in which functional groups acting as dopants are directly or indirectly bonded to the backbone of the conductive polymer via covalent bonds. Examples of functional groups acting as dopants include anionic groups. Anionic groups are groups that acquire a negative charge through the dissociation of cations. Anionic groups can be at least one selected from sulfonic acid groups, phosphate groups, phosphonic acid groups, and carboxyl groups, or their salts (salts with inorganic bases, salts with organic bases, etc.). A preferred example of anionic groups is a sulfonic acid group or a salt thereof.

[0064] Regarding the amount of functional groups (e.g., anionic groups) that function as dopants, the amount relative to the structural unit (monomer unit) of a conductive polymer can be in the range of 0.2 to 3, 0.5 to 2, 0.5 to 1, 1, or less than 1.

[0065] Conductive polymer A can be used alone or in combination with other polymers.

[0066] Examples of the backbone of conductive polymer A include polypyrrole, polythiophene, and polyaniline. These backbones may also contain atomic groups other than functional groups that function as dopants (e.g., functional groups). Examples of conductive polymer A include polypyrroles (polypyrrole and its derivatives) with anionic groups, polythiophenes (polythiophene and its derivatives) with anionic groups, and polyanilines (polyaniline and its derivatives) with anionic groups. In these examples, a preferred example of anionic groups is a sulfonic acid group or its salt. Conductive polymer A can also be a copolymer of two or more monomers.

[0067] For applications requiring higher durability, conductive polymer A can also be a conductive polymer in which atomic groups containing sulfonic acid groups are introduced onto poly(3,4-ethylenedioxythiophene) (PEDOT). For example, conductive polymer A can contain, or be composed of, the following structural units.

[0068] [Chemical Formula 1]

[0069]

[0070] In the above formula, R represents an organic chain. R can be composed of a hydrocarbon chain, or it can contain ether bonds, branched alkyl groups, or other substituents in addition to a hydrocarbon chain. In the above formula, the sulfonic acid group can also be a salt. Examples of R include (skeletal side) -CH2-O-(CH2)2-(CHCH3)-(sulfonic acid group side), etc.

[0071] The following shows an example of a monomer unit of conductive polymer A.

[0072] [Chemical Formula 2]

[0073]

[0074] The content of conductive polymer A in the S-containing conductive polymer is, for example, 15% by mass or more and 60% by mass or less, 15% by mass or more and 45% by mass or less, or 15% by mass or more and 30% by mass or less.

[0075] S-containing conductive polymers can also be further incorporated into non-self-doped conductive polymers (hereinafter also referred to as "conductive polymer B"). Non-self-doped conductive polymers (conductive polymer B) are polymers whose conductivity is improved by doping with dopants.

[0076] Compared to conductive polymer A, conductive polymer B has a greater effect on improving the durability of the solid electrolyte layer. From the perspective of improving the balance between capacity and durability, the sulfur-containing conductive polymer preferably includes both conductive polymer A and conductive polymer B.

[0077] The following description, as typical examples, focuses on the use of conductive polymer A and conductive polymer B as S-containing conductive polymers. The use of conductive polymer A and conductive polymer B in this description is appropriate for understanding the technical meaning of the present invention. However, the present invention is not limited to the use of conductive polymer A and conductive polymer B.

[0078] Non-self-doped conductive polymers (conductive polymer B) exhibit superior durability compared to self-doped conductive polymer A. However, because non-self-doped conductive polymers (conductive polymer B) are dispersed in the liquid medium in a particle-like form, they have difficulty penetrating deep into the porous structure. On the other hand, conductive polymer B can control the extent to which both conductive polymer A and conductive polymer B penetrate deep into the pores.

[0079] When conductive polymer A and conductive polymer B are mixed and the mixture is allowed to permeate into the pores of a porous structure, it is difficult to achieve a sufficient amount of conductive polymer A and conductive polymer B penetrating deep into the pores. Various physical properties need to be controlled, including the compatibility of the mixture of conductive polymer A and conductive polymer B. Furthermore, verification of the physical properties of the porous structures filled with conductive polymers A and B, as well as verification of the capacitance achievement and durability of the electrolytic capacitors, are required.

[0080] Polymer B is also preferred due to its high conductivity. By using a mixture of polymer A and polymer B, an electrolytic capacitor with high conductivity and an excellent balance between capacitance and durability can be obtained.

[0081] The conductivity of conductive polymer B can be above 0.003 S / cm and below 0.3 S / cm, or it can be between 0.01 S / cm and 0.1 S / cm.

[0082] The conductivity of conductive polymer B is determined by coating a dispersion of conductive polymer B onto a flat insulating substrate to form a solid electrolyte layer, and then measuring the conductivity of this solid electrolyte layer. For example, an aqueous dispersion of conductive polymer B is coated onto a flat insulating substrate, dried at 60°C for 10 minutes, then dried at 200°C for 30 minutes, and the conductivity is measured. The conductivity of the solid electrolyte layer can be measured using the Loresta GX and PSP probes manufactured by Nitto Seiko Analytech Co., Ltd.

[0083] In a mixture of conductive polymer A and conductive polymer B, the content of conductive polymer A relative to the total amount of conductive polymer A and conductive polymer B is, for example, 15% by mass or more and 60% by mass or less, 15% by mass or more and 45% by mass or less, or 15% by mass or more and 30% by mass or less.

[0084] The conductive polymer B can also be a polymer material containing conjugated polymers and polymer anions.

[0085] Examples of conjugated polymers include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, and their derivatives. These derivatives include polymers with polypyrrole, polythiophene, polyfuran, polyaniline, and polyacetylene as their basic backbone. For example, derivatives of polythiophene include poly(3,4-ethylenedioxythiophene). A preferred example of a conjugated polymer is poly(3,4-ethylenedioxythiophene) (PEDOT).

[0086] Conjugated polymers can be used alone or in combination. Furthermore, conjugated polymers can also be copolymers of two or more monomers.

[0087] There is no particular limitation on the weight-average molecular weight of conjugated polymers; for example, it can be in the range of 1,000 to 100,000.

[0088] In non-self-doped conductive polymers (conductive polymer B), the functional groups that function as dopants are not covalently bonded to the backbone of the conjugated polymer. For conductive polymer B, the dopant is doped into the conjugated polymer. From the viewpoint of suppressing dedoping from conductive polymer B, polymeric dopants (polymer anions) are preferably used as dopants. That is, conductive polymer B preferably contains both a conjugated polymer and a polymeric anion.

[0089] Examples of polymeric dopants include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly(2-acrylamido-2-methylpropanesulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid. These can be used alone or in combination of two or more. They can also be contained in the electrolyte layer in the form of salts. A preferred example of a polymeric dopant is polystyrene sulfonic acid (PSS).

[0090] There is no particular limitation on the weight-average molecular weight of polymeric dopants; for example, it can be in the range of 1,000 to 100,000. The weight-average molecular weight of polymeric dopants can also be above 1,000 and below 70,000.

[0091] When conductive polymer B is dispersed in a liquid medium in particulate form, the average particle size of the conductive polymer B particles can be 100 nm or more and 500 μm or less, preferably 100 nm or more and 500 nm or less. Conductive polymer B with such an average particle size range is particularly suitable for controlling the S5 and S1 / S5 ratios. The average particle size is the median diameter in the volumetric particle size distribution, as measured by a particle size measuring device based on dynamic light scattering.

[0092] When using a mixture of conductive polymer A and conductive polymer B, the viscosity of the liquid composition containing conductive polymer A and conductive polymer B, measured at 20°C using a rotary type B viscometer, can be, for example, 5 mPa·s or more and 30 mPa·s or less. Liquid compositions with viscosities within this range are particularly suitable for controlling the S5 and S1 / S5 ratios. Regarding the viscosity of the liquid composition, for example, a type B viscometer (DV-2T) manufactured by Eiko Seiki Co., Ltd. is used at a measuring speed of 60 rpm. If the viscosity measured at 20°C is in the range of 1.0 to 10.0 mPa·s, a ULA spindle (diameter 25.13 mm) is sufficient; if the viscosity measured at 20°C is in the range of 10.1 to 100.0 mPa·s, an LV-1 spindle (diameter 18.84 mm) is sufficient.

[0093] Hereinafter, an example of the configuration of the electrolytic capacitor of the present invention will be described in more detail.

[0094] Electrolytic capacitors

[0095] The capacitor element contained in the electrolytic capacitor includes an anode portion and a cathode portion. The cathode portion includes a solid electrolyte layer. Since the solid electrolytic capacitor and capacitor element of the present invention are characterized mainly in the solid electrolyte layer, there are no particular limitations on other constituent elements. Constituent elements used in known electrolytic capacitors can be applied.

[0096] (Capacitor element)

[0097] The anode portion of the capacitor element includes an anode body. A dielectric layer is formed on at least a portion of the surface of the anode body. A cathode portion is formed on at least a portion of the surface of the dielectric layer.

[0098] (Anode)

[0099] The anode body is formed of a conductive material. The anode body can be a sheet-like anode foil, or a shaped or sintered body of metal particles. The anode foil has a core and a porous portion continuous with the core. The sintered body itself can also be porous.

[0100] The average pore diameter (average pit diameter) of the porous section is, for example, 100 nm or more and 1000 nm or less, or 100 nm or more and 200 nm or less. Porous sections with such a range of average pore diameters are particularly suitable for controlling the S5 and S1 / S5 ratios.

[0101] The average pore diameter of the porous section is determined by measuring the pore diameter distribution of the porous section using a mercury porosimeter. Specifically, for each peak appearing in the measured pore diameter distribution curve (vertical axis: log differential pore volume, horizontal axis: pore diameter), the pore diameter corresponding to its peak (the largest peak when multiple peaks exist) is used as the average pore diameter. The measuring device, for example, is the AutoPore V series manufactured by Micromeritics. Based on this pore diameter distribution curve, the pore diameter distribution in the range of less than 2000 nm can be obtained.

[0102] The conductive material constituting the anode body can include a valve-acting metal, an alloy containing a valve-acting metal, or a compound containing a valve-acting metal. The anode body may contain one of these materials or a combination of two or more. For example, aluminum, tantalum, niobium, and titanium are preferred valve-acting metals.

[0103] The anode body has a porous portion, at least on its surface. The porous portion of the anode body has multiple fine pores. Through this porous portion, the anode body has a finely textured, uneven shape.

[0104] An anode with porous surfaces is obtained, for example, by roughening the surface of a substrate containing a valve-acting metal. Roughening can be performed, for example, by etching (electrolytic etching, chemical etching, etc.). Such an anode (anode foil) has, for example, a core and porous portions integrally formed on both sides of the core. The substrate containing the valve-acting metal can be sheet-like, such as a metal foil or a plate-like substrate.

[0105] The anode body can be a sintered or shaped body containing particles of valve-acting metal. Both the shaped and sintered bodies are porous and can be cuboids, cubes, or similar shapes. For example, a sintered body containing tantalum particles can also be used as a sintered body.

[0106] The anode body may have: an anode lead-out portion including a first end, and a cathode forming portion including a second end on the side opposite to the first end. A cathode portion containing a solid electrolyte layer is formed on the surface of the cathode forming portion of the anode body. The anode lead-out portion is used, for example, for electrical connection to an external electrode on the anode side. The anode lead-out portion may also be connected to an anode lead terminal.

[0107] (Anode line)

[0108] When the anode body is a porous sintered or shaped body, the anode portion may include an anode wire. The anode wire may be a metal wire. Examples of materials for the anode wire include the aforementioned valve-acting metal, copper, or copper alloys. A portion of the anode wire is embedded in the anode body, and the remaining portion protrudes outward from one end of the anode body. The end of the anode wire protruding outward corresponds to the first end, and the end of the anode body on the opposite side of the first end corresponds to the second end.

[0109] (Dielectric layer)

[0110] The dielectric layer is formed in such a way that it covers at least a portion of the surface of the anode body or the porous portion. The dielectric layer can be formed using known methods. Alternatively, the dielectric layer can be formed by oxidizing the valve-acting metal on the surface of the anode body or the porous portion using a chemical conversion treatment or similar method. The dielectric layer has a finely textured surface along the shape of the porous portion.

[0111] The dielectric layer contains an oxide of the valve-acting metal. For example, when tantalum is used as the valve-acting metal, the dielectric layer contains tantalum oxide such as Ta₂O₅, and when aluminum is used as the valve-acting metal, the dielectric layer contains aluminum oxide such as Al₂O₃. It should be noted that the dielectric layer is not limited to these examples; it only needs to function as a dielectric.

[0112] (Cathode section)

[0113] The cathode portion includes at least a solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer is formed with the dielectric layer sandwiched between the portion of the solid electrolyte layer on the second end side of the anode body (in other words, the cathode forming portion). The cathode portion typically includes a solid electrolyte layer covering at least a portion of the dielectric layer and a cathode lead-out layer covering at least a portion of the solid electrolyte layer.

[0114] (Solid electrolyte layer)

[0115] In a capacitor element, a solid electrolyte layer is formed to cover at least a portion of the dielectric layer. The solid electrolyte layer in an anode body having a dielectric layer may have a first portion filling the voids within the porous portion and a second portion protruding from the main surface of the anode body having the dielectric layer. As described above, the first portion may contain both self-doped and non-self-doped conductive polymers.

[0116] (Manufacturing method of electrolytic capacitors)

[0117] The method for manufacturing an electrolytic capacitor according to the present invention comprises: a step of preparing an anode body (step (1)), the anode body having a porous portion on at least a portion of its surface covered by a dielectric layer; and a step of forming a solid electrolyte layer (step (2)), the solid electrolyte layer covering at least a portion of the dielectric layer.

[0118] In step (1), an anode body with a porous portion is prepared. The anode body is prepared, for example, by roughening the surface of a metal foil to form a porous portion. The roughening step may include an etching step of etching the metal foil. Through roughening, a porous portion with multiple pits or pores is formed on the surface side of the metal foil. At the same time, a metal core integral with the porous portion is formed on the inner side of the metal foil.

[0119] Etching can be performed, for example, by direct current etching using direct current or alternating current etching using alternating current. In this case, the etching conditions can be controlled so that the average pore diameter (average pit diameter) of the porous portion is, for example, 100 nm or more and 1000 nm or less, preferably 100 nm or more and 200 nm or less.

[0120] The solid electrolyte layer formed in step (2) comprises a sulfur-containing conductive polymer (S-containing conductive polymer). The S-containing conductive polymer fills at least a portion of the voids in the porous portion. The solid electrolyte layer is formed in a manner that satisfies at least one of the above conditions (A) and (B). That is, the sulfur count value S5 detected by EPMA at a depth of 5 μm from the main surface of the porous portion is 12500 or more, or the S5 / S1 ratio is 0.15 or more.

[0121] The process (2) for forming a solid electrolyte layer includes, for example, a process for preparing a liquid composition comprising a liquid medium and an S-containing conductive polymer dispersed in the liquid medium; and a process for impregnating the liquid composition into the porous portion of the anode body.

[0122] Examples of liquid media include water, organic solvents, or mixtures thereof. Water is preferred as the liquid medium.

[0123] As described above, the liquid composition can contain a self-doped conductive polymer (conductive polymer A) and a non-self-doped conductive polymer (conductive polymer B). The polymer chains of conductive polymer A are relatively flexible, and the positions of functional groups such as anionic groups are random. The polymer chains of conductive polymer A have low orientation and low crystallinity. Therefore, compared to conductive polymer B, it is more easily soluble in the liquid medium. Consequently, it easily penetrates deep into the pores of the porous structure with high permeability. On the other hand, conductive polymer B has the effect of inhibiting excessive penetration of conductive polymer A into the deep pores of the porous structure.

[0124] The content of conductive polymer A in the total of conductive polymer A and conductive polymer B can be more than 15% by mass and less than 60% by mass.

[0125] When the average pore diameter of the porous portion of the anode body is 100 nm or more and 1000 nm or less, the average particle size of the conductive polymer B contained in the liquid composition is preferably 100 nm or more and 200 nm or less. In this case, the S5 and S1 / S5 ratio can be easily and appropriately controlled.

[0126] The viscosity of the above-mentioned liquid composition, as measured by a rotational viscometer at 20°C, is preferably 5 mPa·s or more and 30 mPa·s or less. In this case, the S5 and S1 / S5 ratios can be easily and appropriately controlled.

[0127] In the process (2) of forming a solid electrolyte layer, for example, the process of applying the liquid composition to the dielectric layer and then drying it can be repeated more than once.

[0128] The concentration of conductive polymer A in the liquid composition can be, for example, 0.5% by mass or more and 5% by mass or more and 1% by mass or less and 3% by mass.

[0129] The concentration of conductive polymer B in the liquid composition can be, for example, 0.5% by mass or more and 5% by mass or more and 1% by mass or less and 3% by mass.

[0130] Through the above-described process, at least a first portion of the solid electrolyte layer is formed. Then, for example, a treatment solution containing a non-self-doped conductive polymer (conductive polymer B) may be used to form a second portion covering at least a portion of the first portion, protruding from the main surface of the porous portion. More specifically, the second portion can be formed by applying the treatment solution containing conductive polymer B to an anode body having a dielectric layer. If necessary, the application and drying of the treatment solution to the anode body may be repeated more than twice.

[0131] The concentration of conductive polymer B in the treatment solution can be above 0.5% by mass and below 5% by mass, or above 1% by mass and below 3% by mass.

[0132] (Cathode lead-out layer)

[0133] The cathode lead-out layer may, for example, have at least a first lead-out layer that contacts and covers at least a portion of the solid electrolyte layer. The cathode lead-out layer may also have a first lead-out layer and a second lead-out layer that covers at least a portion of the first lead-out layer.

[0134] Examples of first lead-out layers include a layer containing conductive particles and a metal foil. Examples of conductive particles include at least one selected from conductive carbon and metal powder. The cathode portion (more specifically, the cathode lead-out layer) may contain a layer containing metal powder. The cathode lead-out layer may also be composed of a layer containing conductive carbon (carbon layer) as the first lead-out layer and a layer containing metal powder or a metal foil as the second lead-out layer.

[0135] When the cathode lead-out layer comprises a metal foil or a layer containing metal powder, the entire cathode lead-out layer can be constructed from the metal foil or the layer containing metal powder. Alternatively, at least one of the first lead-out layer and the second lead-out layer can be constructed from a layer containing metal powder.

[0136] Examples of conductive carbon include graphite (artificial graphite, natural graphite, etc.).

[0137] The metal powder-containing layer, serving as the second lead-out layer, can be formed, for example, by laminating a metal powder-containing composition onto the surface of the first lead-out layer. Such a second lead-out layer can be formed, for example, using a paste containing metal powder and a resin binder. Thermoplastic resins can also be used as the resin binder, but thermosetting resins such as imide resins and epoxy resins are preferred.

[0138] From the viewpoint of easily obtaining high conductivity in the second lead layer, silver-containing particles can be used as the metal powder. Examples of silver-containing particles include silver particles and silver alloy particles. The second lead layer may contain one type of silver-containing particle, or it may contain two or more types in combination. The silver particles may also contain a small amount of impurities.

[0139] When using a metal foil as the first lead-out layer, the type of metal is not particularly limited. Valve-acting metals (aluminum, tantalum, niobium, etc.) or alloys containing valve-acting metals are preferred. The surface of the metal foil may be roughened as needed. A chemical conversion coating or a coating of a different metal (dissimilar metal) or non-metal may be provided on the surface of the metal foil. Examples of dissimilar metals or non-metals include metals such as titanium or non-metals such as carbon (conductive carbon, etc.).

[0140] Alternatively, the film of the aforementioned dissimilar metal or non-metal (e.g., conductive carbon) can be used as the first lead-out layer, and the aforementioned metal foil can be used as the second lead-out layer.

[0141] (other)

[0142] An electrolytic capacitor contains at least one capacitor element. Electrolytic capacitors can be wound, chip, or laminated. For example, an electrolytic capacitor can also contain multiple laminated capacitor elements. Additionally, an electrolytic capacitor can contain two or more wound capacitor elements. The configuration of the capacitor elements depends on the type of electrolytic capacitor.

[0143] When a metal foil is used as the cathode lead-out layer, a spacer can also be provided between the metal foil and the anode foil, which serves as the anode body. There are no particular limitations on the spacer; for example, a nonwoven fabric containing fibers such as cellulose, polyethylene terephthalate, vinylon, or polyamide (e.g., aliphatic polyamide, aromatic polyamide, etc.) can be used.

[0144] In a capacitor element, one end of a cathode lead terminal can be electrically connected to the cathode lead layer. Regarding the cathode lead terminal, for example, a conductive adhesive is applied to the cathode lead layer, and the cathode lead terminal is bonded to the cathode lead layer via this conductive adhesive. One end of an anode lead terminal can be electrically connected to the anode lead portion of the anode body. The other ends of the anode lead terminal and the other ends of the cathode lead terminal extend from the resin outer casing or housing, respectively.

[0145] The other end of each terminal exposed from the resin outer casing or housing is used for solder connection to the substrate on which the electrolytic capacitor is to be mounted. In addition, not limited to the case of leading out the lead terminals, at least one end face of the anode and cathode may be exposed from the outer surface of the seal and electrically connected to an external electrode.

[0146] The capacitor element is sealed using a resin casing or housing. For example, the capacitor element and the resin material of the casing (e.g., uncured thermosetting resin and filler) can be housed in a mold, and the capacitor element can be sealed with a resin casing using transfer molding, compression molding, or similar methods. In this case, the portions of the anode lead terminals and cathode lead terminals connected to the anode leads extending from the capacitor element are exposed from the mold. Alternatively, the capacitor element can be housed in a bottomed housing with the portions of the anode and cathode lead terminals located at the opening of the bottomed housing, and the opening of the bottomed housing can be sealed with a sealing material to form an electrolytic capacitor. The leads can be wire-like or frame-like (lead frame, etc.).

[0147] Figure 1This is a cross-sectional schematic diagram of an electrolytic capacitor according to one embodiment of the present invention. The electrolytic capacitor 1 includes: a capacitor element 11, a resin casing 12 sealing the capacitor element 11, and an anode terminal 13 and a cathode terminal 14 exposed outside the resin casing 12. The capacitor element 11 includes: an anode body 2, a dielectric layer 3 covering a second end side of the anode body 2, and a cathode portion 15 covering the dielectric layer 3. The portion of the anode body 2 where the cathode portion 15 (particularly the solid electrolyte layer 4) is formed is a cathode forming portion, and the portion where the cathode portion 15 is not formed is an anode lead-out portion. The anode terminal 13 is electrically connected to the anode lead-out portion of the anode body 2. The cathode terminal 14 is electrically connected to the cathode portion 15. The resin casing 12 has a generally cuboid shape, thus the solid electrolytic capacitor 1 also has a generally cuboid shape.

[0148] The anode 2 and the cathode 15 are positioned opposite each other, separated by a dielectric layer 3. The cathode 15 has a solid electrolyte layer 4 covering the dielectric layer 3 and a cathode lead-out layer 5 covering the solid electrolyte layer 4. The cathode lead-out layer 5 in the example figure has a two-layer structure and has a carbon layer 5a in contact with the solid electrolyte layer 4 and a metal particle-containing layer 5b covering the surface of the carbon layer 5a.

[0149] In the anode lead-out portion of the anode body 2 protruding from the cathode portion 15, an insulating separation portion 16 is formed in a strip-like manner covering the surface of the anode body 2 in the region on the cathode portion 15 side, thus restricting contact between the cathode portion 15 and the anode body 2. The first end (anode lead-out portion) of the anode body 2 protruding from the cathode portion 15 is electrically connected to one end 13a of the anode terminal 13 by welding or the like. On the other hand, the cathode lead-out layer 5 formed on the outermost layer of the cathode portion 15 is electrically connected to one end 14a of the cathode terminal 14 via a conductive adhesive 17 (e.g., a mixture of thermosetting resin and metal particles). The other end 13b of the anode terminal 13 and the other end 14b of the cathode terminal 14 are respectively led out from different sides of the resin outer casing 12, extending to a main flat surface in an exposed state. Figure 1 (The middle is the lower surface). The exposed portions of each terminal on this flat surface are used for solder connection to the substrate (not shown) on which the solid electrolytic capacitor 1 is to be mounted.

[0150] The dielectric layer 3 is formed on a portion of the surface of the conductive material constituting the anode body 2. Specifically, the dielectric layer 3 can be formed by anodizing the surface of the conductive material constituting the anode body 2. Therefore, the dielectric layer 3 is formed along the surface of the anode body 2 (including the holes or recessed inner wall surfaces of the more inner surfaces).

[0151] (Postscript)

[0152] Based on the above description, the following technologies were disclosed.

[0153] (Technology 1)

[0154] An electrolytic capacitor comprising:

[0155] An anode body having a porous portion of its surface covered by a dielectric layer, and

[0156] A solid electrolyte layer covering at least a portion of the aforementioned dielectric layer.

[0157] The aforementioned solid electrolyte layer contains a conductive polymer containing sulfur.

[0158] The aforementioned sulfur-containing conductive polymer fills at least a portion of the voids in the aforementioned porous portion.

[0159] The sulfur element count S5, detected by an electron beam microanalyzer at a depth of 5 μm from the main surface of the porous section, is 12500 or higher.

[0160] (Technology 2)

[0161] An electrolytic capacitor comprising:

[0162] An anode body having a porous portion of its surface covered by a dielectric layer, and

[0163] A solid electrolyte layer covering at least a portion of the aforementioned dielectric layer.

[0164] The aforementioned solid electrolyte layer contains a conductive polymer containing sulfur.

[0165] The aforementioned sulfur-containing conductive polymer fills at least a portion of the voids in the aforementioned porous portion.

[0166] The ratio (S5 / S1) of the sulfur element count value S5 detected by an electron beam micro analyzer at a depth of 5 μm from the main surface of the porous portion to the sulfur element count value S1 detected by an electron beam micro analyzer at a depth of 1 μm from the main surface of the porous portion is 0.15 or higher.

[0167] (Technology 3)

[0168] According to the electrolytic capacitor of technology 1 or 2, the ratio (S10 / S5) of the sulfur element count value S10 detected by an electron beam microanalyzer at a depth of 10 μm from the main surface of the porous portion is 0.3 or more.

[0169] (Technology 4)

[0170] According to the electrolytic capacitor of technology 3, the ratio of S10 to S5 (S10 / S5) is 0.5 or less.

[0171] (Technology 5)

[0172] The electrolytic capacitor according to any one of techniques 1 to 4, wherein the sulfur-containing conductive polymer contains a self-doped conductive polymer.

[0173] (Technology 6)

[0174] According to the electrolytic capacitor of technology 5, the content of the self-doped conductive polymer in the sulfur-containing conductive polymer is 15% by mass or more and 60% by mass or less.

[0175] (Technology 7)

[0176] According to the electrolytic capacitor of technique 5 or 6, the aforementioned sulfur-containing conductive polymer further contains a non-self-doped conductive polymer.

[0177] (Technology 8)

[0178] According to the electrolytic capacitor of Technique 7, the non-self-doped conductive polymer comprises a conjugated polymer and a polymer anion.

[0179] (Technology 9)

[0180] The electrolytic capacitor according to any one of techniques 1 to 8, wherein the conductivity of the aforementioned non-self-doped conductive polymer is 0.003 S / cm or more and 0.3 S / cm or less.

[0181] (Technology 10)

[0182] The electrolytic capacitor according to any one of techniques 1 to 9, wherein the average pore diameter of the porous portion is 100 nm or more and 1000 nm or less.

[0183] (Technology 11)

[0184] A method for manufacturing an electrolytic capacitor, comprising:

[0185] A process for preparing an anode body, the anode body having a porous portion on its surface covered by a dielectric layer; and

[0186] The process of forming a solid electrolyte layer, wherein the solid electrolyte layer covers at least a portion of the aforementioned dielectric layer.

[0187] The aforementioned solid electrolyte layer contains a conductive polymer containing sulfur.

[0188] The aforementioned sulfur-containing conductive polymer fills at least a portion of the voids in the aforementioned porous portion.

[0189] The ratio (S5 / S1) of the sulfur element count value S5 detected by an electron beam micro analyzer at a depth of 5 μm from the main surface of the porous portion to the sulfur element count value S1 detected by an electron beam micro analyzer at a depth of 1 μm from the main surface of the porous portion is 0.15 or higher.

[0190] (Technology 12)

[0191] According to the method for manufacturing an electrolytic capacitor as described in Technique 11, wherein,

[0192] The process of forming a solid electrolyte layer includes: a process of preparing a liquid composition comprising a liquid medium and a conductive polymer containing sulfur dispersed in the liquid medium; and

[0193] The process of permeating the above-mentioned liquid composition into the porous portion of the above-mentioned anode body.

[0194] (Technology 13)

[0195] According to the method for manufacturing an electrolytic capacitor as described in Technique 12, the viscosity of the liquid composition, as measured by a rotational viscometer at 20°C, is 5 mPa·s or more and 30 mPa·s or less.

[0196] (Technology 14)

[0197] The method for manufacturing an electrolytic capacitor according to technique 12 or 13, wherein the liquid composition comprises a self-doped conductive polymer and a non-self-doped conductive polymer.

[0198] (Technology 15)

[0199] According to the manufacturing method of the electrolytic capacitor of technology 14, the content of the self-doped conductive polymer in the total of the self-doped conductive polymer and the non-self-doped conductive polymer is 15% by mass or more and 60% by mass or less.

[0200] [Example]

[0201] The present invention will now be described in detail based on embodiments and comparative examples, but the present invention is not limited to the following embodiments.

[0202] Example 1

[0203] Construct capacitor components according to the following guidelines and evaluate their characteristics.

[0204] (1) Preparation of an anode with a dielectric layer

[0205] An anode body with a core and porous sections formed on both sides of the core is fabricated by roughening the two surfaces of an aluminum foil (thickness: 100 μm) used as a substrate through etching. The average pore diameter of the porous sections is 150 nm.

[0206] (2) Process of forming dielectric layer

[0207] The anode body is immersed in a chemical conversion solution and a DC voltage of 70V is applied for 20 minutes to form a dielectric layer containing aluminum oxide.

[0208] (3) Process of forming a solid electrolyte layer

[0209] (3-1) Preparation of liquid compositions

[0210] As S-containing conductive polymers, the following self-doped conductive polymers (conductive polymer A) and non-self-doped conductive polymers (conductive polymer B) were prepared.

[0211] <Conductive Polymer A>

[0212] An aqueous solution of conductive polymer A, composed of the following monomer units, was prepared.

[0213] [Chemical Formula 3]

[0214]

[0215] <Conductive Polymer B>

[0216] An aqueous dispersion of poly(3,4-ethylenedioxythiophene) (PEDOT), doped with polystyrene sulfonic acid (PSS), was prepared. The average particle size of PEDOT / PSS, determined by the above method, was 150 nm.

[0217] Conductive polymer A and conductive polymer B were mixed to prepare a liquid composition containing water as a liquid medium and S-containing conductive polymer dispersed in the water. The content of S-containing conductive polymer in the liquid composition was set to 30% by mass. The mass content (Cs) of conductive polymer A in the total mass of conductive polymers A and B was set as shown in Table 1.

[0218] The viscosity of the liquid composition, measured by a vibratory viscometer at 20°C under the above conditions, is shown in Table 1. Additionally, an aqueous dispersion of conductive polymer B was coated onto a flat insulating substrate, dried at 60°C for 10 minutes, and then dried at 200°C for 30 minutes to form a solid electrolyte layer. The conductivity B of this solid electrolyte layer is shown in Table 1.

[0219] (3-2) Impregnation and drying of liquid composition

[0220] A liquid composition is prepared in a container. Then, at room temperature and atmospheric pressure, the anode body with a dielectric layer is immersed in the liquid composition in the container for 1 minute. The anode body is then removed from the liquid composition and dried in a drying oven at 120°C for 10–30 minutes, filling the pores of the porous portion of the anode body with an S-containing conductive polymer to form a solid electrolyte layer.

[0221] (4) The process of forming the cathode lead-out layer

[0222] The anode obtained in (3) above is immersed in a dispersion obtained by dispersing graphite particles in water. After being removed from the dispersion, it is dried, thereby forming a carbon layer 5a on the surface of the solid electrolyte layer. The drying is carried out at 130-180°C for 10-30 minutes.

[0223] Next, a silver paste containing silver particles and an adhesive resin (epoxy resin) is coated onto the surface of the carbon layer 5a, and heated at 150–200°C for 10–60 minutes to cure the adhesive resin, forming a metal particle-containing layer 5b. Thus, a cathode lead-out layer 5 consisting of the carbon layer 5a and the metal particle-containing layer 5b is formed. The capacitor element 11 is then fabricated as described above.

[0224] (5) Assembly of electrolytic capacitors

[0225] The cathode lead-out layer 5 of the capacitor element 11 obtained in (4) above is joined to one end 14a of the cathode terminal 14 using a conductive adhesive 17. The anode lead-out portion of the anode body 2 protruding from the capacitor element 11 is joined to one end 13a of the anode terminal 13 by laser welding. Thus, the electrolytic capacitor E1 of Example 1 is completed. Resin sealing is not performed.

[0226] Examples 2-4, Comparative Examples 1-4

[0227] Except for varying the mass content (Cs) of conductive polymer A in the total of conductive polymer A and conductive polymer B, the viscosity of the liquid composition (or the molecular weight of each conductive polymer), and the conductivity B of the solid electrolyte layer, the electrolytic capacitors E2 to E4 of Examples 2 to 4 and the electrolytic capacitors R1 to R4 of Comparative Examples 1 to 4 were completed in the same manner as in Example 1.

[0228] (6) Evaluation

[0229] (6-1) Capacity Achievement Rate

[0230] Before forming the solid electrolyte layer, the anode body was immersed in a 15% (w / w) ammonium adipate aqueous solution, and the capacitance (C100) at a rated voltage of 120 Hz was determined. Then, a solid electrolyte layer was formed on the anode body, and after forming the cathode lead-out layer, the capacitance (Cn) at a rated voltage of 120 Hz was determined using an LCR meter. The ratio of Cn to C100 was used as the capacity achievement rate (Cr). The results are shown in Table 1.

[0231] (6-2) Charge and discharge characteristics

[0232] Repeat the charging and discharging of the electrolytic capacitor (ON (applied rated voltage) / OFF = 1 second / 1 second) for 10,000 cycles, and calculate the ratio (ΔCap) of the difference between the capacitance (C0) before the charge-discharge cycle and the capacitance (C10000) after the charge-discharge cycle (C0 - C10000) to C0. The results are shown in Table 1.

[0233] (6-3) Heat resistance and durability

[0234] The electrolytic capacitors were stored at 145°C, and their equivalent series resistance (ESR) was measured after 500 hours. The results are shown in Table 1.

[0235] [Table 1]

[0236]

[0237] Figure 2 The diagram shows the relationship between the depth of the anode body of electrolytic capacitors E1 and R1 from the main surface of the porous section and the sulfur (S) count value detected by an electron beam microanalyzer. In E1, the count value S5 shows a large value exceeding 12500, and the S5 / S1 ratio exceeds 0.15. On the other hand, in R1, the count value S5 is below 12500, and the S5 / S1 ratio is less than 0.15. Based on this difference, it can be considered that there is a difference in the capacitance achievement rate and durability of the electrolytic capacitors.

[0238] While the invention has been described in conjunction with presently preferred embodiments, such disclosure should not be interpreted as restrictive. Various modifications and alterations will become apparent to those skilled in the art upon reading the foregoing disclosure. Therefore, the appended claims should be construed as encompassing all modifications and alterations without departing from the true spirit and scope of the invention.

[0239] Industrial availability

[0240] The electrolytic capacitor of the present invention is suitable for applications requiring high reliability.

[0241] Explanation of reference numerals in the attached figures

[0242] 1: Electrolytic capacitor

[0243] 2: Anode body

[0244] 3: Dielectric layer

[0245] 4: Solid electrolyte layer

[0246] 5: Cathode lead-out layer

[0247] 5a: Carbon layer

[0248] 5b: Layer containing metal particles

[0249] 11: Capacitor Components

[0250] 12: Resin outer casing

[0251] 13: Anode terminal

[0252] 13a: One end of the anode terminal

[0253] 13b: The other end of the anode terminal

[0254] 14: Cathode terminal

[0255] 14a: One end of the cathode terminal

[0256] 14b: The other end of the cathode terminal

[0257] 15: Cathode section

[0258] 16: Separation section

[0259] 17: Conductive adhesives

Claims

1. An electrolytic capacitor comprising: An anode body having a porous portion of its surface covered by a dielectric layer, and A solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer contains a conductive polymer containing sulfur. The sulfur-containing conductive polymer fills at least a portion of the voids in the porous portion. The sulfur element count S5, detected by an electron beam microanalyzer at a depth of 5 μm from the main surface of the porous section, is greater than 12500.

2. An electrolytic capacitor, comprising: An anode body having a porous portion of its surface covered by a dielectric layer, and A solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer contains a conductive polymer containing sulfur. The sulfur-containing conductive polymer fills at least a portion of the voids in the porous portion. The ratio S5 / S1 of the sulfur element count value S5 detected by an electron beam micro analyzer at a depth of 5 μm from the main surface of the porous portion and the sulfur element count value S1 detected by an electron beam micro analyzer at a depth of 1 μm from the main surface of the porous portion is greater than or equal to 0.

15.

3. The electrolytic capacitor according to claim 1 or 2, wherein, The ratio of the sulfur element count value S10 to S5, measured by an electron beam microanalyzer at a depth of 10 μm from the main surface of the porous section, is greater than or equal to 0.

3.

4. The electrolytic capacitor according to claim 3, wherein, The ratio of S10 to S5, S10 / S5, is less than 0.

5.

5. The electrolytic capacitor according to claim 1 or 2, wherein, The sulfur-containing conductive polymer contains a self-doped conductive polymer.

6. The electrolytic capacitor according to claim 5, wherein, The content of the self-doped conductive polymer in the sulfur-containing conductive polymer is 15% by mass or more and 60% by mass or less.

7. The electrolytic capacitor according to claim 5, wherein, The sulfur-containing conductive polymer also contains non-self-doped conductive polymers.

8. The electrolytic capacitor according to claim 7, wherein, The non-self-doped conductive polymer comprises conjugated polymers and polymer anions.

9. The electrolytic capacitor according to claim 1 or 2, wherein, The conductivity of the non-self-doped conductive polymer is above 0.003 S / cm and below 0.3 S / cm.

10. The electrolytic capacitor according to claim 1 or 2, wherein, The average pore diameter of the porous portion is above 100 nm and below 1000 nm.

11. A method for manufacturing an electrolytic capacitor, comprising: A process for preparing an anode body, the anode body having a porous portion on its surface covered by a dielectric layer; and The process of forming a solid electrolyte layer, wherein the solid electrolyte layer covers at least a portion of the dielectric layer. The solid electrolyte layer contains a conductive polymer containing sulfur. The sulfur-containing conductive polymer fills at least a portion of the voids in the porous portion. The ratio S5 / S1 of the sulfur element count value S5 detected by an electron beam micro analyzer at a depth of 5 μm from the main surface of the porous portion and the sulfur element count value S1 detected by an electron beam micro analyzer at a depth of 1 μm from the main surface of the porous portion is greater than or equal to 0.

15.

12. The method for manufacturing an electrolytic capacitor according to claim 11, wherein, The process of forming a solid electrolyte layer includes: A step of preparing a liquid composition comprising a liquid medium and a conductive polymer containing the sulfur element dispersed in the liquid medium; and The process of permeating the liquid composition into the porous portion of the anode body.

13. The method for manufacturing an electrolytic capacitor according to claim 12, wherein, The viscosity of the liquid composition, measured at 20°C using a rotary B-type viscometer, is greater than 5 mPa·s and less than 30 mPa·s.

14. The method for manufacturing an electrolytic capacitor according to claim 12 or 13, wherein, The liquid composition comprises self-doped conductive polymers and non-self-doped conductive polymers.

15. The method for manufacturing an electrolytic capacitor according to claim 14, wherein, The self-doped conductive polymer accounts for more than 15% by mass and less than 60% by mass in the total of the self-doped conductive polymer and the non-self-doped conductive polymer.

Citation Information

Patent Citations

  • Electrolytic capacitor and method for manufacturing electrolytic capacitor

    JP2022161723A

  • Semiconductor device

    JP2024052417A